Menelisik Sumbangan Islam Bagi Peradaban Modern - Wahyudin Noor (Faculty of Da’wa and Islamic Communication, State Institute for Islamic Studies of Syaikh Abdurrahman Siddik Bangka Belitung, 2017)
Islamic contributions to modern civilization, include: first, the contribution of Islam in modern science in a system of belief based on monotheism; secondly, in the political sphere, that Islam and democracy are essentially compatible, viable, and should be seen as a continuation or development of the Islamic